Rekomendasi Peningkatan Kualitas Layanan Publik di Institusi X Provinsi Jawa Barat Berdasarkan Analisis Kesenjangan Persepsi dan Harapan Pengguna - Fiday Zulfan Al-Bantany; Yoanita Yuniati Mukti (Journal of Science, Technology, and Innovation, 2026)
The service managed by Institution X in West Java Province is a public service that requires continuous improvement in service quality, including the identification of priority aspects that need to be improved. Previous issues included long waiting times, limited system access, technical disruptions, and insufficient staff responsiveness, indicating the need for continuous quality improvement. This study aimed to provide recommendations for service quality improvement based on the results of Gap 5 analysis, which measures the difference between user perceptions and expectations. The study employed a quantitative approach using five SERVQUAL dimensions: tangibles, reliability, responsiveness, assurance, and empathy. Data were collected through a questionnaire that had been tested for validity and reliability and was completed by 255 service users. The results showed an average Gap 5 score of 0.012, indicating that overall service performance had met user expectations, although this achievement was not consistent across all attributes. Improvement priorities were determined based on attributes with negative gap scores, namely computer equipment and system performance (-0.008) and waiting time (-0.004). These two attributes had not yet met user expectations due to the limited number of computers and staff, delayed device response, and network connection constraints. Further improvement should be undertaken by management through an analysis of the gap between management perceptions of user expectations and the actual expectations of users regarding these two attributes.